Mite fauna associated with different environments of Brazilian Pampa and a case of predatory mite impairing the control of invasive plant - Toldi, Maicon (2019)
The Brazilian Pampa is predominantly a natural pasture region with gallery forest formations. It conserves a rich biodiversity and provides vast biological resources for economic use. Pampa suffers from the replacement of fields by grain crops and tree planting to obtain cellulose. The objectives of this work were to evaluate the composition of the mites community comparing the different environments; to relate mite fauna to microclimatic factors and to know the interactions between mites/plants; description of new species and evaluate the biology of Euseius stipulatus (Athias-Henriot) and Typhlodromus (Typhlodromus) exhilaratus Ragusa feeding on Aculus mosoniensis Ripka (Eriophyidae) from an invasive plant Ailanthus altissima (Mill.) Swingle (Simaroubaceae). Mites were collected from the most representative plant species in the Grassland, Grazing Exclusions and Riparian Forest environments of Pampa biome. To evaluate the diversity of mites between enviroments, the ANOSIM test was used at a significance level of 5%. Four new species of eriophyoid mites were described and illustrated. Regarding the predators Phytoseiidae and Stigmaeidae, the Riparian Forest environment had the highest abundance (72%), followed by Grazing Exclusions (20%) and Pastures (8%). One hundred seventeen species of mites were collected in the three environments, being the majority phytophagous (57%). The Riparian Forest environment forms an independent grouping from Grazing Exclusions and Grassland. The species responsible for the similarity of the Grassland and Grazing Exclusions environments was Tydeus californicus (Banks), while to the Riparian Forest, Brachytydeus formosa (Cooreman) was the most significant. Air humidity and soil correlated with Riparian Forest indicators, while active photosynthetic effects, temperature and higher wind velocity correlated with Grassland and Grazing Exclusions. Euseius stipulatus may make hinder the biological control of invasive plant A. altissima. The three environments presented mite species with a high number of plant interactions, greater than ten. Mites were indicators responding to environmental differences evaluated Grassland, Grazing Exclusions and Riparian Forest.